Acute two-photon imaging of the neurovascular unit in the cortex of active mice - Tran, Cam Ha T.; Gordon, Grant R. (Frontiers in Cellular Neuroscience, 2015)
In vivo two-photon scanning fluorescence imaging is a powerful technique to observe physiological processes from the millimeter to the micron scale in the intact animal. In neuroscience research, a common approach is to install an acute cranial window and head bar to explore neocortical function under anesthesia before inflammation peaks from the surgery. However, there are few detailed acute protocols for head-restrained and fully awake animal imaging of the neurovascular unit during activity. This is because acutely performed awake experiments are typically untenable when the animal is naïve to the imaging apparatus. Here we detail a protocol that achieves acute, deep-tissue two-photon imaging of neocortical astrocytes and microvasculature in behaving mice. A week prior to experimentation, implantation of the head bar alone allows mice to train for head-immobilization on an easy-to-learn air-supported ball treadmill. Following just two brief familiarization sessions to the treadmill on separate days, an acute cranial window can subsequently be installed for immediate imaging. We demonstrate how running and whisking data can be captured simultaneously with two-photon fluorescence signals with acceptable movement artifacts during active motion. We also show possible applications of this technique by 1) monitoring dynamic changes to microvascular diameter and red blood cells movements in response to vibrissa sensory stimulation, 2) examining responses of the cerebral microcirculation to the systemic delivery of pharmacological agents using a tail artery cannula during awake imaging, and 3) measuring Ca2+ signals from synthetic and genetically encoded Ca2+ indicators in astrocytes. This method will facilitate acute two-photon fluorescence imaging in awake, active mice and help link cellular events within the neurovascular unit to behaviour.